THE ROLE OF BACTERIAL VAGINOSIS IN PRETERM LABOR - S. V. Apresyan; V. F. Arakelyan; A. A. Abashidze (IRBIS LLC, 2016)
Infections associated with pregnancy, labor and postpartum period pose a threat to the pregnant woman, fetus and newborn baby and remain a serious issue for physicians over several centuries. The preterm labor which often may not have a clear etiology is the major cause of neonatal deaths worldwide. The relationship between changes in vaginal microbiocenosis and preterm labor is not sufficiently well studied so far.